PENINGKATAN KECERDASAN VISUAL SPASIAL ANAK USIA DINI MELALUI PERMAINAN MAZELAILY ROSIDAH - ROSIDAH, LAILY (Program Studi Magister Pendidikan Anak Usia Dini, 2014)
This research is motivated by the lack of visual spatial ability in kindergarten childrenUtsmanil Judge, Land Sareal-Bogor. It is seen from them is takes of students in determining theright-left direction, recognize colors and difficulty remembering and classifying children ingeometric shapes. This study aimsto improv echildren's visual-spatial intelligence through amazegame. This research was conducted in kindergarten Utsmanil Judge, Land Sareal-Bogor withchild research subjects 12 peoplein Mayand June 2014 This study used aqualitative approach toaction research method. The results showed the maze games can improve children's visual-spatialintelligence. It can be seen from the increase obtained from the firs tcycleby 33.43% on average sothat thes patial intelligence of children 77.7%. While the initialconditions of the average visualspatial intelligence before the child's actions amounted to44.27%. After the second cycle the nanincrease of 7:19%, so the average value ofchildren's visual-spatial intelligence obtained in thesecond cycle was 84.89%. In this study it can be concluded that thev isual-spatial intelligence canbe improved through a maze game. Conducting a maze madeeveryday with avariety of differentmedia as well as individual activities carried ou tby the group know. Keyword: Visual Spatial Intelligence, Playing Maze, Early Childhood Abstrak: Penelitian ini dilakukan, karena rendahnya kemampuan visual spasial anak di TKUtsmanil Hakim, Tanah Sareal-Bogor. Siswa belum bisa menentukan arah kanan-kiri, mengenalwarna, kesulitan mengingat dan mengelompokkan bentuk geometri. Penelitian ini bertujuan untukmeningkatkan kecerdasan visual spasial anak melalui permainan maze. Penelitian ini dilakukan diTK Utsmanil Hakim, Tanah Sareal-Bogor dengan subjek penelitian 12 anak. Penelitian inimenggunakan pendekatan kualitatif dengan metode action research. Hasil penelitian menunjukkanpermainan maze yang dibuat berbagai modifikasi dapat meningkatkan kecerdasan visual spasialanak. Rata-rata kecerdasan visual spasial anak pra tindakan adalah sebesar 44.27%. Peningkatanpada siklus pertama sebesar 33.43 % sehingga rata-rata kecerdasan spasial anak sebesar 77,7%.Siklus kedua terjadi peningkatan sebesar 7.19%, sehingga nilai rata-rata kecerdasan visual spasialanak yang diperoleh pada siklus kedua sebesar 84.89%. Kata kunci: Kecerdasan Visual Spasial, Permainan Maze, Anak Usia Dini